An Intervention Study in Healthy Booklet of Child Under Five Years in Baubau City - Asriadi; Risna; Usman (MIRACLE Journal Of Public Health, 2021)
Utilization healthy booklet the provision of information to mothers of child under 5 years of age who have Maternal Child Healthy Booklet with additional information of nutritional intake or local supplementary feeding, health care, stimulation and visit to posyandu (center of integrated health services) through the lecture questioning method with using modules and leaflets. This study aims to determine the intervention utilization healthy booklet against growth and development of child under 5 years of age. The type of research used in this study is quasi experiment with non-randomized pre-test-post-test control group design. Sampling technique is exhaustive sampling amounted to 100 respondents. Where there are 2 groups (intervention and control), each amounted to 50 respondents. The result showed that there was a significant difference of knowledge (p=0.000), attitude (p=0.000) and practice (p=0.000) of before and after obtaining intervention. Conclution in this study is utilization maternal child Healthy Booklet more effective to improve linear retradation and cognition of child under 5 years of age at Baubau City.